A Contrastive Study on Feminisms between œPerempuan Berkalung Sorban Novel and The Color Purple Novel. - Wilanda, Vitta; Tetty, Morada; Manullang, Elisa Betty (TRANSFORM: Journal of English Language Teaching and Learning, 2021)
This research discussed about Feminismin both selected novels PerempuanBerkalung Sorban and The Color Purplewhich aimed at finding out the types offeminism, reason why can the figure ofwomen struggle of feminisms and the roleof women in both of the selected novels.This research was based on Tong™s theory.This research was conducted by usingdescriptive qualitative method. The datawere taken from both selected novelswhich have feminisms, they arePerempuan Berkalung Sorban and TheColor Purple Novel. The findings showedthat there were 28 data, 24 data in types offeminism in Perempuan Berkalung Sorbanand The Color Purple Novel.The dominanttypes from both the novels is LiberalFeminisms in Perempuan BerkalungSorban Novel, because the first characterfrom Perempuan Berkalung Sorban Novelis Annisa who feels unfair treatment shereceives from her family;and there were 4data in the role of women in domesticsector can struggle in PerempuanBerkalung Sorban and The Color PurpleNovel. The researcher concluded thesimilar types of feminism, they were:Liberal Feminism and Radical Feminism